2018
DOI: 10.1021/acssuschemeng.8b03331
|View full text |Cite
|
Sign up to set email alerts
|

Dual Cross-linked Epoxidized Natural Rubber Reinforced by Tunicate Cellulose Nanocrystals with Improved Strength and Extensibility

Abstract: Cellulose nanocrystals have been proved to be ideal reinforcing fillers for rubber. However, the increase in tensile strength always accompanies a reduction in extensibility. In this paper, epoxidized natural rubber (ENR) nanocomposites with dual cross-linking networks by incorporating tunicate cellulose nanocrystals (t-CNs) were prepared. Carboxyl groups were introduced onto t-CNs surface via grafting reaction with maleic anhydride (MAH). Interfacial chemical reaction between carboxyl groups on modified t-CNs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(71 citation statements)
references
References 56 publications
(97 reference statements)
6
65
0
Order By: Relevance
“…Nanocellulose exhibits some exclusive features such as exceptional mechanical properties (i.e., low density, high flexibility, and strength while being chemically inert) (Lavoine and Bergström, 2017) and thermal properties (Gan et al, 2020). Over the past few decades, many research studies have been conducted on the reinforcement of polymer matrix nanocomposites, for instance, natural rubber nanocomposites (Neto et al, 2016;Cao et al, 2018;Dominic et al, 2020), polylactic acid nanocomposites (Gitari et al, 2019;Rigotti et al, 2019), epoxy nanocomposites (Ayrilmis et al, 2019;Yan et al, 2019;Yue et al, 2019), and polystyrene nanocomposites (Clarke et al, 2019;Neves et al, 2019), where nanocellulose has been introduced as a reinforcing agent.…”
Section: Properties and Surface Modification Of Nanocellulose Charactmentioning
confidence: 99%
“…Nanocellulose exhibits some exclusive features such as exceptional mechanical properties (i.e., low density, high flexibility, and strength while being chemically inert) (Lavoine and Bergström, 2017) and thermal properties (Gan et al, 2020). Over the past few decades, many research studies have been conducted on the reinforcement of polymer matrix nanocomposites, for instance, natural rubber nanocomposites (Neto et al, 2016;Cao et al, 2018;Dominic et al, 2020), polylactic acid nanocomposites (Gitari et al, 2019;Rigotti et al, 2019), epoxy nanocomposites (Ayrilmis et al, 2019;Yan et al, 2019;Yue et al, 2019), and polystyrene nanocomposites (Clarke et al, 2019;Neves et al, 2019), where nanocellulose has been introduced as a reinforcing agent.…”
Section: Properties and Surface Modification Of Nanocellulose Charactmentioning
confidence: 99%
“…Surface modification of nanocellulose can also lead to good thermal properties especially with hydrophobic polymer matrices. According to Cao et al ., the introduction of carboxyl groups into CNC could produce a nanocomposite with enhanced thermal characteristics. The reinforcement of modified CNC enhanced the T g notably.…”
Section: Thermal Properties Of Nanocellulose Compositesmentioning
confidence: 99%
“…In addition, some investigations also involve the addition of foreign reagents to improve interactions between the nanofiller and the rubber matrix, either through surface modification of NCs or adding dispersants in rubber latex. For instance, Cao et al [ 120 ] used carboxylated tunicate CNC in ENR matrices and observed concentration-dependent improvements of crosslink density and an approximate 50% improvement of the tensile strength (from 2.3 MPa to 3.5 MPa) when compared to unmodified tunicate CNC at 5 phr loading. This was attributed to the orientation of modified CNC and rubber chains, which induced stronger interfacial covalent bonds for effective stress transfer at the filler-matrix interfaces.…”
Section: Properties Improvement Of Nanocellulose-reinforced Rubbermentioning
confidence: 99%